Pengaruh Pemberdayaan Perempuan Dalam Ekonomi Dan Politik Terhadap Pembangunan Perempuan di Provinsi Sumatera Barat - Elsa Yunara; Isra Yeni; Muhammad Irfan Irfan (Universitas Negeri Padang, 2023)
Sustainable economic development requires people who are able and empowered to meet their needs and escape from poverty. It can be seen that the HDI for women is always below the HDI for men every year. This study aims to identify women's empowerment in the economy and politics can improve women's development in West Sumatra. With the Panel Least Squares (PLS) method then proceed with the classical assumption test, with a panel regression model. Research on 19 districts/cities in West Sumatra with a span of 5 years. The results showed that female professional staff, women's income contribution had a positive and significant effect on women's development, women entrepreneurs had a negative and insignificant effect on women's development, women in parliament had a positive and insignificant effect on women's development in West Sumatra. It can be concluded that women's empowerment in the economy and politics is very important for the development of a country. From the results of this study it is suggested to the government to pay more attention to women's empowerment so as to achieve women's development and improve gender-equitable welfare